The effect of minibars basalt fiber fraction on mechanical properties of high-performance concrete. Issue 1 (31st December 2022) - Abbas Ashour Alaraza, Hayder; Kharun, Makhmud; Chiadighikaobi, Paschal Chimeremeze
Abstract: Basalt fiber (BF) is one of the most important sustainable materials used to enhance high-performance concrete (HPC) in recent years. There are two types of BF, namely micro-BF and macro-BF. Despite that, macro-BF is a new material and there are few studies about it. A variety of standard material tests were carried out to examine the impact of MiniBars BF as well as its fractions (0.6–1.8%) on the physical and mechanical properties of HPC, including compressive strength f c m, flexural strength ( f f ), workability, and modulus of elasticity ( E c ). The study applied the one variable at a time method by using an identical mix with different fractions of MiniBars BF to minimize the influence of other factors on the result of the test. Six different mixes were investigated. The experiment showed that the MiniBars BF fraction slightly affected the workability of the HPC mix. The results indicated that the small amount of MiniBars BF did not affect the f c m and the E c of HPC. But it has a negative effect after the dosage of MiniBars BF increased by more than 1.2%. The MiniBars BF enhanced the f f significantly even with a small percentage until it reached the optimum effect at 0.9% then drop slightly.